To study the correlation between fine needle aspiration cytology and histopathological findings of breast tumours, to identify the commonest risk factors and to analysis its association with the total peripheral, lymphocyte count. - Pandey, Jagat Singh (2001)
ABSTRACT: The main objective of this study was to see the correlation between fine needle aspiration cytology (FNAC) and histopathological findings of breast tumors, to identify the commonest risk factors and to analyse its association with total peripheral lymphocyte count. FNAC was done in 40 cases with clinically palpable breast lump in pathology department of TUTH from April 2000 to March 2001 (one year). These slides were stained with Giemsa and Papanicolaus stains. The histological specimens of the same individual who underwent FNAC were subsequently studied. Blood samples of the patients also were taken for total leukocyte count & differential count. Total count was done by counter. Out of 40 cases, 23 (57.5%) were found to be cytologically being and 17 (42.5%) were malignant. The commonest benign condition diagnosed cytologically was fibroadenoma (27.5%) and malignant condition was infiltrating ductal carcinoma. (IDC) Cyto-histological correlation was done in all 40 cases. Out of 23 cases diagnosed as benign in FNAC, histological findings showed benign in 20 cases and 3 turned out to be malignant. So, there were 3 (7.5%) false negative cases. All 17 cases diagnosed as malignant cytologically, proved to be malignant histologically. The correlation between FNAC and histopathology showed sensitivity 85% and specificity 100%. Histologically, commonest benign lesion was fibroadenoma (40%) and commonest malignant lesion was IDC 70%. The mean age for benign lesion was 29.3 years and malignant lesion it was 46.85years. The study did not show any correlation with family history, early menarche and late menopause, late age at first childbirth, use of contraceptives, obesity and decreased total peripheral lymphocyte count in breast carcinoma significantly, probably because the sample size was too small. At the same time, poverty, illiteracy and socio-cultural values of the subjects must have also played the important role for not showing the correlation.